2021
DOI: 10.1088/1361-648x/abf19b
|View full text |Cite
|
Sign up to set email alerts
|

Hot-phonon effects in photo-excited wide-bandgap semiconductors

Abstract: Carrier and lattice relaxation after optical excitation is simulated for the prototypical wide-bandgap semiconductors CuI and ZnO. Transient temperature dynamics of electrons, holes as well as longitudinal-optic (LO), transverse-optic (TO) and acoustic phonons are distinguished. Carrier-LO-phonon interaction constitutes the dominant energy-loss channel as expected for polar semiconductors and hot-phonon effects are observed for strong optical excitation. Our results support the findings of recent time-resolved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 68 publications
1
2
0
Order By: Relevance
“…Based on a model calculation, Herrfurth et al . found that the relaxation of hot carriers in CuI is dominated by carrier-LO-phonon interaction and the hot-phonon effect can delay the relaxation process by few picoseconds 70 , which is in good agreement with our findings.
Fig.
…”
Section: Resultssupporting
confidence: 92%
“…Based on a model calculation, Herrfurth et al . found that the relaxation of hot carriers in CuI is dominated by carrier-LO-phonon interaction and the hot-phonon effect can delay the relaxation process by few picoseconds 70 , which is in good agreement with our findings.
Fig.
…”
Section: Resultssupporting
confidence: 92%
“…During this transition, electron vacancies, commonly referred to as "holes" (h+), and an excess of electrons (e-) are created within the material. The use of nanoparticles as photo-catalysts is a highly beneficial approach to harness the physical and optical properties of semiconductors, as described in [14][15][16]. NPs incorporated into a photo-catalyst are extremely tiny particles, typically in the nanometer scale.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the electron drift velocity as a function of electric field was determined. Non-equilibrium (hot) longitudinal optical (LO) phonons were found to slow down hot-electron energy relaxation in ZnO [17,18] and limit electron transport in ZnO 2DEG channels [19]. Hot-phonon decay gets faster and hot-electron velocity is increased at some resonance sheet electron density [12,20,21].…”
Section: Introductionmentioning
confidence: 99%